2019
DOI: 10.1080/17425247.2019.1563070
|View full text |Cite
|
Sign up to set email alerts
|

Toward a new age of patient centricity? The application of eye-tracking to the development of connected self-injection systems

Abstract: Background: Increasing interest in digitally enhanced drug delivery tools urges both industry and academia to rethink current approaches to product usability testing. This article introduces mobile eyetracking, generating detailed contextual data about user engagement with connected self-injection systems as a new methodological approach to formative usability assessment. Methods: A longitudinal case study with a total of 35 injection-naïve participants was conducted. In three consecutive experiments, eye-trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
(68 reference statements)
1
11
0
Order By: Relevance
“…This makes it difficult to identify the root causes of usability problems and thus the necessary changes in UI design. In alignment with Lohmeyer et al [ 31 ] and Koester et al [ 30 ], this study showed that mobile eye tracking provides objective quantitative results based on physiological measurements related to individual UI features. These results can be used to evaluate usability in much more detail compared with traditional methods.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This makes it difficult to identify the root causes of usability problems and thus the necessary changes in UI design. In alignment with Lohmeyer et al [ 31 ] and Koester et al [ 30 ], this study showed that mobile eye tracking provides objective quantitative results based on physiological measurements related to individual UI features. These results can be used to evaluate usability in much more detail compared with traditional methods.…”
Section: Discussionsupporting
confidence: 78%
“…More complex subjects of the investigations include graphical UIs such as computer tomography interfaces [ 26 ] or spacecraft displays [ 27 , 28 ]. Further, there are single studies where eye tracking is used to evaluate highly interactive UIs of tangible products like smart TVs [ 29 ], smartwatches [ 12 , 21 ], or medical devices [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…A range of works based on the use of gaze information for consumer platforms like automotive (for driver monitoring), augmented and virtual reality (for foveated rendering and immersive experiences), smartphones and TV (for gaze based menu selection and navigation) have been described in our review [4]. Recent works in this field include [7] where gaze duration and patterns are used to assess how easily users can navigate an interface of a connected selfinjection system. Gaze data is used as an indicator to study the usability, efficiency and ease of use of the drug delivery device.…”
Section: Prior Art In Gaze Data Analysis Softwarementioning
confidence: 99%
“…A useful tool to overcome this challenge is eye tracking, which enables to uncover common problems during the use of medical devices [15], provides valuable objective insights for user interface design [16] and allows to assess the effectiveness of trainings [17]. It proves as a successful skill and training assessment tool, [18] is applicable in medical education, [19] and allows for comparison between expert and novice surgeons [20][21][22].…”
Section: Introductionmentioning
confidence: 99%